Pengaruh Corporate Social Responsibility (CSR), Struktur Modal Dan Likuiditas Terhadap Kinerja Keuangan: Penelitian - Af’idatul Kamila; Dedi Rusdi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to analyze the influence of Corporate Social Responsibility (CSR), capital structure, and liquidity on financial performance. The research method employed a quantitative approach, utilizing secondary data from the financial statements of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The research sample was selected using a purposive sampling technique, resulting in 27 companies meeting the criteria, resulting in 81 observational data sets. Data processing was performed using multiple linear regression analysis with the aid of SPSS version 26 software. The results showed that Corporate Social Responsibility (CSR), capital structure, and liquidity had a positive and significant effect on financial performance. Simultaneously, these three variables proved to have a positive impact on financial performance. Future research suggests the addition of other variables, such as good corporate governance, while companies are expected to be more consistent in presenting financial reports and sustainability reports.